1 Peter and Christ’s descent to the dead in its early Christian reception - Lei, C-K (2023)
1 Peter 3:19 is traditionally the major scriptural support for the doctrine of Christ’s descent to the dead (descensus). Present scholarship, however, tends to detach 1 Peter 3:19 from the descensus. The dominant interpretation assumes that the text speaks of Christ’s ascent in proclaiming victory over the fallen angels, and that no association between 1 Peter 3:19 and the descensus existed before the third century. No previous study, however, has focused on how and why 1 Peter 3:19 came to be associated with the descensus in its early reception, nor what bearing the descensus could have on the text of 1 Peter 3:19 itself. Thus, this thesis fills this lacuna by studying 1 Peter’s early reception in relation to the descensus with Origen as the watershed. Chapter 1 introduces the state of scholarship on the relationship between 1 Peter 3:19 and the descensus, as well as the methodology used in this thesis. Chapter 2 begins with a brief survey of twenty early Christian sources which speak about the descensus from a variety of traditions outside 1 Peter, ranging retrospectively from third-century Origen to first-century Paul. Chapter 3 explores the possibility of a second-century reception of 1 Peter 3:19 in relation to the descensus. By analysing two second-century texts, the “Jeremiah logion” and the Gospel of Peter 41-42, I argue for a second-century reception of 1 Peter in relation to the descensus through an organic and dynamic memory of Peter associated with apocalyptic revelation. Chapter 4 discusses Clement’s and Origen’s receptions of 1 Peter 3:19 in relation to the descensus, arguing that both writers stretch 1 Peter 3:19 to the limit of its exegetical boundary. Chapter 5 explores the possible genesis of Clement’s and Origen’s interpretations of 1 Peter 3:19 in relation to the descensus. I argue that their interpretations of 1 Peter 3:19 are indebted to a kind of apocalyptic Petrine memory, which should be seen in line of the Enochic tradition situated within the broader Tour of Hell tradition. Chapter 6 concludes the whole thesis.